Evaluation of Yield Components of New Sweet Corn Hybrids in Bogor, Indonesia - Aprilianti, Devi Kurnia; Syukur, Muhamad; Suwarno, Willy Bayuardi (Department of Agronomy and Horticulture, IPB University, 2016)
The demand of sweet corn in Indonesia has been increasing; therefore breeding efforts are aimed for high yielding sweet corn varieties with superior quality. This research was aimed to evaluate the yield of five newly developed sweet corn hybrids compared to the commercial varieties. The research was conducted at the Leuwikopo experimental field of IPB, and Laboratory of Genetics and Plant Breeding, Department of Agronomy and Horticulture, IPB Darmaga campus from September to December 2015. The experiment was arranged in a completely randomized block design with three replications. Five new sweet corn hybrids, “ JM8 x JM2”, “JM8 x JM7”, “JM16 x JM8”, “JM17 x JM6” and “JM17 x JM7”, and four commercial varieties, “Bonanza”, “Master Sweet”, “Sugar 75” and “Sweet Boy”, were tested. The results showed that the new hybrids vary in plant height, days to anthesis, days to silking, ear height, ear length, sugar content, number of kernel rows, the weight of husked ear, and number of ears per plant, downy mildew infected area, and productivity. F1 of “JM8 x JM2” has longer ears than “Master Sweet” and “Sugar 75”, higher sugar content than “Sugar 75”, and higher resistance against downy mildew than “Master Sweet” and “Sweet Boy”.